The Influence of the Korean Series "Start Up" on Interest in Entrepreneurship at the Student Level Case Study of Albert Bandura's Social Cognitive Theory - Ericka Caesaria Hanifah Andrian; Nala Nandana Undiana (Cinematology: Journal Anthology of Film and Television Studies, 2021)
In this study the author tries to investigate how impactful a korean drama titled “Start Up” to its audience on their interest of starting up a business with Social Cognitive Theory by Albert Bandura as the theoretical framework. This study uses the quantitative approach by holding up a survey aimed to college students. The finding suggests that most of the respondents are intrigued in staring up a business after watching the drama. But we can’t say that it’s the only reason behind it as internal factors, experiences, and their environment also take parts in shaping up their mind and deciding what they are going to do. Keywords — start up, korean drama, social cognitive theory